Effect of Traditional Chinese Medicine nursing combined with continuous nebulization in nursing of elderly patients undergoing tracheostomy (中医护理联合持续雾化吸入在老年气管切开患者护理中的应用效果观察) - HUANG Ning (黄宁) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) nursing combined with continuous nebulization in nursing of elderly patients undergoing tracheostomy. Methods Totally 60 patients aged 60 years or older with cerebral hemorrhage, respiratory failure, coma and other diseases were included as research subjects. According to the order of tracheotomy, 30 patients with odd numbers were included as the control group and 30 patients with even number were included as the study group. The control group received routine ICU care and intermittent nebulization inhalation for 15～20 minutes each, and number of nebulization was adjusted on the basis of sputum viscosity. The study group received TCM nursing intervention combined with continuous nebulization. The duration of lung infection and retention time of tracheotomy catheter were compared between both groups were compared between two groups. The incidence of high sputum viscosity, respiratory tract irritation symptoms, airway mucosal damage and sputum blockage were observed during follow-up. Results Shorter duration of lung infection and retention time of tracheotomy catheter were observed in the study group than those in the control group (P<0. 05). There were fewer patients with high sputum viscosity, respiratory irritation symptoms, airway mucosal damage or sputum blockage in the study group than those in the control group respectively (P <0. 01). Conclusion For elderly patients with tracheotomy in the ICU hospitalization, TCM nursing intervention combined with continuous nebulization not only effectively reduce the incidence of high sputum viscosity, respiratory irritation symptoms, airway mucosal damage and sputum blockage, but also shorten the duration of lung infection and retention time of tracheotomy catheter. It could help to promote patient recovery and clinical curative effect. (目的 探讨中医护理联合持续雾化吸入在老年气管切开患者护理中的应用效果。方法 选取医院重症监护室2021年7月—2022年6月收治的脑出血、呼吸衰竭、昏迷等患者60例(年龄≥60岁), 均行气管切开术。根据气管切开的先后顺序, 奇数纳入对照组(n=30), 偶数纳入观察组(n=30)。对照组给予ICU常规护理和间断雾化吸入, 每次15～20 min, 并根据痰液黏稠度增加或减少雾化的次数; 观察组给予中医护理联合持续雾化吸入治疗。对比两组肺部感染持续时间和气管切开导管留置时间, 观察和分析患者痰液黏稠、呼吸道刺激症状、气道黏膜损伤、痰阻发生情况。结果 观察组患者肺部感染持续时间和气管切开导管留置时间均较对照组缩短, 差异有统计学意义(P<0. 05)。观察组患者痰液黏稠度、呼吸道刺激症状、气道黏膜损伤以及痰阻发生例数少于对照组, 差异有统计学意义(P<0. 01)。结论 给予老年气管切开患者中医护理联合持续雾化吸入治疗, 符合患者的生理需求, 不仅能改善患者痰液黏稠、呼吸道刺激症状、气道黏膜损伤、痰阻情况, 还能减少患者肺部感染的持续时间, 缩短患者气管切开导管的留置时间, 有助于促进患者康复。)